INCLUSIVE LEADERSHIP AS AN HR DEVELOPMENT IMPERATIVE: A LONGITUDINAL STUDY ON ITS EFFECT ON PSYCHOLOGICAL SAFETY AND TEAM INNOVATION - Kartika Simanjuntak; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The increasing diversity of the modern workforce has intensified the need for inclusive leadership as a critical capability for organizational success. While existing research highlights the benefits of inclusive leadership, limited attention has been given to its long-term effects on team dynamics and innovation. This study examines the impact of inclusive leadership on psychological safety and team innovation using a longitudinal research design. Data were collected from teams across multiple time points to capture changes in leadership behaviors and team perceptions. The findings indicate that inclusive leadership significantly enhances psychological safety by fostering trust, openness, and reduced fear of failure. Psychological safety, in turn, mediates the relationship between leadership and team innovation, enabling increased idea generation and implementation. The results also show that the effects of inclusive leadership strengthen over time, leading to sustained innovation performance. The study contributes to the literature by providing a dynamic perspective on leadership and team outcomes. It also offers practical implications for HR development by emphasizing the importance of continuous investment in inclusive leadership. The findings suggest that organizations can enhance innovation and performance by fostering psychologically safe environments through inclusive leadership practices.